2010
DOI: 10.1016/j.expneurol.2010.08.005
|View full text |Cite
|
Sign up to set email alerts
|

Sleep alterations in an environmental neurotoxin-induced model of parkinsonism

Abstract: Parkinson's disease (PD) is classically defined as a motor disorder resulting from decreased dopamine production in the basal ganglia circuit. In an attempt to better diagnose and treat PD before the onset of severe motor dysfunction, recent attention has focused on the early, non-motor symptoms, which include but are not limited to sleep disorders such as excessive daytime sleepiness (EDS) and REM behavioral disorder (RBD). However, few animal models have been able to replicate both the motor and non-motor sy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
23
0

Year Published

2012
2012
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 29 publications
(24 citation statements)
references
References 26 publications
(36 reference statements)
1
23
0
Order By: Relevance
“…Mice fed washed cycad flour display a progressive phenotype with some PD-like symptoms including degeneration of DAergic neurons of the SNpc and cognitive deficits as shown by increased latency to find the platform in a water-maze task and an increased number of errors in a radial-arm maze (Wilson et al, 2002). Cycad-fed rats show a progressive loss of DAergic neurons of the SNpc, aSyn accumulation in multiple brain regions, and early alterations of sleep/wake activity characterized by an increase in SWS and REM sleep during the active phase (McDowell et al, 2010; Shen et al, 2010). This model provides a different approach with which to study the progressive neurodegeneration observed in PD, also enabling for the stable detection of NMS.…”
Section: The Non-motor Features Of Toxin-induced Parkinsonismmentioning
confidence: 99%
“…Mice fed washed cycad flour display a progressive phenotype with some PD-like symptoms including degeneration of DAergic neurons of the SNpc and cognitive deficits as shown by increased latency to find the platform in a water-maze task and an increased number of errors in a radial-arm maze (Wilson et al, 2002). Cycad-fed rats show a progressive loss of DAergic neurons of the SNpc, aSyn accumulation in multiple brain regions, and early alterations of sleep/wake activity characterized by an increase in SWS and REM sleep during the active phase (McDowell et al, 2010; Shen et al, 2010). This model provides a different approach with which to study the progressive neurodegeneration observed in PD, also enabling for the stable detection of NMS.…”
Section: The Non-motor Features Of Toxin-induced Parkinsonismmentioning
confidence: 99%
“…Similarly, MPTP injection disrupts normal muscle atonia during paradoxical sleep in the marmoset, reminiscent of RBD (Verhave et al, 2011). Paradoxical sleep is also reduced in the mouse, rat and cat following MPTP injection (Pungor et al, 1990; Lima et al, 2007; Laloux et al, 2008a; McDowell et al, 2010). This effect appears to extend to other, less common neurotoxins; ingestion of the environmental toxin cycad causes hypersomnolescence as evidenced on EEG in rats (McDowell et al, 2010).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…As outlined above, administration of toxins that target dopaminergic neurons result in sleep abnormalities in a range of animal models (Barraud et al, 2009; Verhave et al, 2011; Lima et al, 2007; Pungor et al, 1990; McDowell et al, 2010; Laloux et al, 2008a). In fact, administration of MPTP directly to the substantia nigra results in a decrease in REM sleep and a decrease in sleep latency (Lima et al, 2007).…”
Section: Parkinson’s Diseasementioning
confidence: 99%
“…The various REM-related sleep problems have been replicated in MPTP-treated marmosets, providing support for the notion that they are caused by disturbances in DA transmission [29]. Hypersomnolent behavior with an increase in the duration and the number of spells of REM sleep and non-REM sleep suggest that an inability to maintain wakefulness have been reproduced in cycad-fed rats [108]. This excessive daytime sleepiness has been attributed to dysregulation of orexin neurons as the cycad-fed rats demonstrate loss of orexin cells in the hypothalamus.…”
Section: Sleep Disturbancesmentioning
confidence: 73%